Comparative analysis of molecular mechanisms of relaxation of DNA bending deformation - Shashel, Ya.V.; Smyrnova, D.O. (Харьковский Национальный Университет им. В.Н.Каразина, 2010)
Comparison of relaxation mechanisms of bending DNA deformation was performed by molecular dynamics method for two types of bending DNA from complex with 434 repressor and purine repressor. Comparative analysis of relaxation dynamics of local structure parameters characterizing DNA structure on dinucleotide level and parameters characterizing DNA structure as whole was performed. Obtained data shows that relaxation takes place in stages and each stage is characterized by similar time intervals for two bending DNA types. It is shown that character of relaxation in the initial stages of dynamics depends on the type of DNA bending deformation: for smooth curve linear changes in parameters are peculiar; for localized sharp curve changes in parameters occurs abruptly.
Keywords: DNA; molecular dynamics; protein-nucleic acids interactions; structure deformations; relaxation mechanisms